2007
DOI: 10.1152/jn.00212.2007
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Silent Synapses Into the Active Pool by Selective GluR1-3 and GluR4 AMPAR Trafficking During In Vitro Classical Conditioning

Abstract: Mokin M, Zheng Z, Keifer J. Conversion of silent synapses into the active pool by selective GluR1-3 and GluR4 AMPAR trafficking during in vitro classical conditioning. J Neurophysiol 98: 1278 -1286, 2007. First published June 27, 2007 doi:10.1152/jn.00212.2007. The conversion of silent synapses into active sites is hypothesized to be a primary mechanism underlying learning and memory processes. Here we used an in vitro model of classical conditioning from turtles that demonstrates a neural correlate of eyebli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 47 publications
7
45
0
Order By: Relevance
“…We reported previously that preexisting GluR1 AMPAR subunits are delivered to silent synapses during early stages of conditioning, followed by synthesis and insertion of GluR4 subunits that support CR acquisition (Mokin et al, 2007). In the present study, bath application of BDNF for the equivalent of two pairing sessions induced the same postsynaptic glutamate receptor modifications that was observed after two sessions of conditioning.…”
Section: Bdnf-induced Trafficking Of Glur1 and Glur4 Amparssupporting
confidence: 76%
See 4 more Smart Citations
“…We reported previously that preexisting GluR1 AMPAR subunits are delivered to silent synapses during early stages of conditioning, followed by synthesis and insertion of GluR4 subunits that support CR acquisition (Mokin et al, 2007). In the present study, bath application of BDNF for the equivalent of two pairing sessions induced the same postsynaptic glutamate receptor modifications that was observed after two sessions of conditioning.…”
Section: Bdnf-induced Trafficking Of Glur1 and Glur4 Amparssupporting
confidence: 76%
“…In previous studies we consistently observed that levels of the presynaptic protein synaptophysin were significantly elevated during conditioning Mokin et al, 2007). Western blotting was performed to assess whether BDNF induces a similar enhancement of presynaptic proteins.…”
Section: Bdnf-induced Expression Of Presynaptic Proteins Synaptophysimentioning
confidence: 87%
See 3 more Smart Citations